Mandatory disclosure and financial contagion - Fernando Alvarez; Gadi Barlevy (Federal Reserve Bank of Chicago, 2014)
This paper analyzes the welfare implications of mandatory disclosure of losses at financial institutions when it is common knowledge that some banks have incurred losses but not which ones. We develop a model that features contagion, meaning that banks not hit by shocks may still suffer losses because of their exposure to banks that are. In addition, we assume banks can profitably invest funds provided by outsiders, but will divert these funds if their equity is low. Investors thus value knowing which banks were hit by shocks to assess the equity of the banks they invest in. We find that when the extent of contagion is large, it is possible for no information to be disclosed in equilibrium but for mandatory disclosure to increase welfare by allowing investment that would not have occurred otherwise. Absent contagion, mandatory disclosure cannot raise welfare, even if markets are frozen.
Keywords: G01; G14; G17; 330; Information; Networks; Contagion; Stress Tests